The Biological Functions of MBL-Associated Serine Proteases (MASPs) - Hajela, Krishnan; Kojima, Mayumi; Ambrus, Geza; Nicky Wong, K.H.; Moffatt, Beryl E.; Ferluga, Janez; Hajela, Sumati; Gál, Peter; Sim, Robert B. (Immunobiology (1979), 2002)
The Mannose-binding lectin-associated serine proteases (MASPs) have been the subject of intensive research particularly over the past 10 years. First one, then two, and currently 3 MASPs have been characterized. Initially it was thought likely that the MBL+MASPs system would resemble very closely the C1 complex of the complement classical pathway, and that MASP1 and MASP2 would have similar activities to their classical pathway homologues C1r and C1s. MASP2 does certainly have similar activities to C1s, but MASP1 does not have the activities of either C1r or C1s. MASP1 has been thought to act on the complement system by cleaving C3 directly, but work with recombinant and purified native MASP1 shows that direct C3 cleavage by this protease is very slow, and may not be biologically significant. MASP1 and MASP2 appear not to have such a narrow specificity as C1r and C1s, and may have significant substrates other than complement proteins. As an example, MASP1 does cleave fibrinogen, releasing fibrinopeptide B (a chemotactic factor) and also cleaves and activates plasma transglutaminase (Factor XIII). These reactions are also relevant to defence against microorganisms, and may represent a biologically significant action of MASP1.